2015
DOI: 10.1177/1753193415579300
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of functional and aesthetically outcomes of reverse digital artery and reverse dorsal homodigital island flaps for fingertip repair

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 31 publications
2
31
0
2
Order By: Relevance
“…Regarding gender, this study included six male patients (75%), in line with other studies. 2 , 14 As for the side, the left hand was affected in most cases (62.5%). This variable diverges from the results of the study by Huang et al, 8 which showed 52.5% of cases on the right limb and 47.5% on the left.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding gender, this study included six male patients (75%), in line with other studies. 2 , 14 As for the side, the left hand was affected in most cases (62.5%). This variable diverges from the results of the study by Huang et al, 8 which showed 52.5% of cases on the right limb and 47.5% on the left.…”
Section: Discussionmentioning
confidence: 96%
“…Local flaps are preferred due to technical simplicity, and the fact that the receiving area has the same characteristics. 3 , 4 , 5 , 12 , 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Описано множество методов лечения -от простых консервативных, до сложных -с при-менением микрохирургической техники [11,36,60,70,77,87,88,98,108,144,162]. Не всегда ясно, по какому принципу авторы отдают пред-почтение той или иной методике.…”
Section: методы лечения травм дфпunclassified
“…Несмотря на большое количество предло-женных методов закрытия дефектов кончиков пальцев, армаментарий лоскутов или их модифи-каций продолжает расти, сo значительным улуч-шением функциональных и эстетических исхо-дов лечения [35,36,64,78,90,112,117,128,132,139,155].…”
Section: методы лечения травм дфпunclassified